Remy Belleau et l'art de guérir - Braybrook, Jean (De Gruyter, 2013)
This book fills a gap in the market as it ranges over the whole of Belleau's work, rather than concentrating solely on La Bergerie or Les Amours et nouveaux eschanges des pierres precieuses. It starts by asking why a group of doctors produced a French edition of Belleau in 1945. It moves on to consider sickness and healing in Belleau's work, studying the comedy, La Reconnue, and the macaronic poem, the Dictamen metrificum, alongside the better-known texts. Throughout, it emphasizes the importance of the political and religious background of the time. A miraculous stick that Belleau describes in La Bergerie is seen in the first chapter of L'Art de guérir as a symbol of therapeutic powers. The second chapter considers love and the poet's debt to other writers, such as Sappho or Ficino (Belleau was erudite and eclectic). Les Amours de David et de Bersabee is the focal point of Chapter 3; once again one sees the corrosive powers of love, and the ability of poetry and music to transform suffering into beauty. Mention is made of the various academies, which were important in Belleau's development. Chapter 4 traces the motif of illness in La Reconnue and links it to religious turmoil. This connection is even clearer in the Dictamen metrificum de bello huguenotico, a strange, savagely humorous text (Chapter 5). Chapter 6 concerns Belleau's poems on precious stones, surely the pinnacle of his achievement. In those, therapy is an explicitly articulated motif, while religious faith is crucial. The conclusion suggests parallels with writers such as Saint Augustine, Rabelais, Du Bellay and Montaigne.